Utilization of Micronized Polyethylene Terephthalate (MPET) as a Filler in Asphalt Pavement - Gungat, Lillian; Amrah, Khairul Ikhwan; Moris, Mouren; Abdullah, Noor Halizah (International Journal of Sustainable Construction Engineering and Technology, 2023)
Nowadays, plastic pollution is one of the most critical issues related to sustainability development that need to be solved. Studies indicated that addition of certain amount of recycled plastic from Polyethylene Terephthalate (PET) in asphalt mixture has improved the engineering properties such as marshall stability, moisture resistance, rutting and fatigue resistance. However, the main challenge of direct incorporation of recycled plastic in binder is the thermal incompatibility of two phases which are glass transition and melting temperature. Previous research findings indicated that reduction in particles diameter to micro scale would decrease the PET melting point. Hence, this study investigates the potential of micronized PET from recycled plastic bottle as filler in asphalt pavement. Micronization process at laboratory was carried out to determine the appropriate method prior incorporating it into asphalt mixture. The micronized size of PET incorporated at 0%, 4%, 8%, and 12% by weight of filler is then evaluated for its volumetric properties, mechanical, and adhesion properties. The results showed that the volumetric properties of the asphalt were affected by the presence of micronized PET. The mechanical properties in terms of Resilient Modulus and Indirect Tensile Strength showed increment with addition of micronized PET. Similar trend also observed on adhesion properties. Hence, the findings indicated the potential of utilizing the recycled MPET for local road construction.